PENGGUNAAN SOFTWARE GEOGEBRA UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS MAHASISWA - Batubara, Ismail Hanif; Sari, Indah Purnama (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2020, 2021)
The purpose of this study was to determine whether the increase in mathematical problem-solving abilities of students who were given the help of Geogebra software was higher than the problem-solving abilities of students without the help of Geogebra software. This research is quasi-experimental research. This study's population were all classes of the third-semester mathematics education study program, totalling approximately 60 people. The experimental class was given learning treatment using GeoGebra software as a learning medium, while the control class was not given learning treatment with the help of GeoGebra software. Data analysis was performed by t-test. The results showed that the increase in the mathematical problem-solving ability of the group of students who received learning using Geogebra software was higher than the group of students who received learning without Geogebra software.